A New 2D Supramolecular Cd(II) Network Constructed by Mixed Ligand. Issue 1 (2nd January 2016) - Wei-Ping, Wu; Jun, Wang; Lu, Lu; Bin, Xie; Xiulan, Zhang
Abstract : A new coordination network, namely [Cd(pda)(IP)(H2 O)] (1 ) (H2 pda = pyrazine-2, 3-dicarboxylic acid and IP= 1- H -imidazo[4, 5-f][1, 10]-phenanthroline), is explored. A 2D supramolecular net is formed by the hydrogen bonding interactions between IP and coordination water molecule and between carboxylate ligand and water molecule. The luminescence study indicates that the title compound emits bright fluorescence.